The Use Of Medicinal Plants During The Covid-19 Pandemic: Perspective Of Literacy And Consumption Interests For Millennial Generation - Dudi Septiadi; Mohammad Archi Maulyda; Arif Widodo (JURNAL AGRIBISNIS TERPADU, 2020)
Medicinal plants are returning viral during the Covid-19 pandemic. The absence of effective vaccines and drugs to ward off Covid-19 has increased interest in consuming medicinal plants. The trend of consuming medicinal plants during a pandemic cannot be separated from the role of the millennial generation. The millennial generation has more capabilities than the older generation in accessing and disseminating information. The problem is whether the millennial generation uses technology to support literacy about medicinal plants? How is the use of medicinal plants among the millennial generation? This research uses a descriptive qualitative approach. Data collection through surveys. The instrument used was a questionnaire. The number of respondents involved was 90 people. The characteristics of the research respondents are population aged 20-43 years in 2020. Based on the results of the study, it can be seen that the level of literacy of the millennial generation towards medicinal plants is low. The level of literacy is inversely proportional to the quite high interest in consuming medicinal plants. Millennial generations tend to consume medicinal plants just because they follow the trend. The millennial generation is more affected by everything viral on social media. The willingness to find the truth of information is still low. There is a gap between the level of literacy and the consumption interest of the millennial generation in consuming medicinal plants during the Covid-19 Pandemic.